2009
DOI: 10.1097/aln.0b013e318195b51d
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine and Dexmedetomidine Produce Antinociceptive Synergy in Mouse Spinal Cord

Abstract: Background Synergy between drugs manifests with increased potency and/or efficacy of the combination relative to either agonist given alone. Synergy is typically observed between drugs of different classes, as is the case with the alpha-adrenergic-opioid receptor synergy often observed in preclinical studies. However, rare studies report synergy between agonists of the same class. The present study examined the analgesic interaction between two intrathecally injected alpha-2 adrenergic receptor (AR) agonists p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 50 publications
2
23
1
Order By: Relevance
“…Its molecular mechanism has been investigated by animal models, Yuan et al (32) reported that dexmedetomidine could prevent RIH via regulating spinal NMDA receptor trafficking as well as protein kinase C and calmodulin-dependent protein kinase II pathway. This result was consistent with other animal studies that suggested combination of α2 adrenergic receptor agonist with an opioid can increase analgesic potency to some extent (33,34). Moreover, by effectively suppressing glial cell proliferation and activate the adjacent nerve cells involved in peripheral and central sensitization, dexmedetomidine has been shown effectively decreasing hyperalgesia by increasing acetylcholine levels in the spinal cord (35).…”
Section: Discussionsupporting
confidence: 81%
“…Its molecular mechanism has been investigated by animal models, Yuan et al (32) reported that dexmedetomidine could prevent RIH via regulating spinal NMDA receptor trafficking as well as protein kinase C and calmodulin-dependent protein kinase II pathway. This result was consistent with other animal studies that suggested combination of α2 adrenergic receptor agonist with an opioid can increase analgesic potency to some extent (33,34). Moreover, by effectively suppressing glial cell proliferation and activate the adjacent nerve cells involved in peripheral and central sensitization, dexmedetomidine has been shown effectively decreasing hyperalgesia by increasing acetylcholine levels in the spinal cord (35).…”
Section: Discussionsupporting
confidence: 81%
“…The kappa 1 and α 2 adrenergic drugs require their respective receptors for activity. Clonidine analgesia was markedly impaired in α 2A receptor knockout mice (24) and U50,488H analgesia was lost in a kappa opioid receptor knockout mouse (25,26). Furthermore, it is unlikely they directly label the 6TM target based on the poor affinity of both clonidine and U50,488H for the E11 binding site in brain labeled by 125 I-IBNtxA (10).…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine has α2:α1 binding selectivity ratio of 1620:1 compared to 220:1 for clonidine [5], and more predictable pharmacokinetic properties compared to clonidine [9,10]. It also possesses selective α2-adrenoceptor agonism, especially for the 2A subtype of this receptor, which causes it to be a much more effective sedative and analgesic agent than clonidine [11,12].…”
Section: Introductionmentioning
confidence: 99%